2021
DOI: 10.3390/vaccines9060553
|View full text |Cite
|
Sign up to set email alerts
|

Pfizer-BioNTech COVID-19 Vaccine Tolerance in Allergic versus Non-Allergic Individuals

Abstract: Individuals with a history of allergy are potentially at risk of suffering from adverse effects after COVID-19 vaccination. We sought to assess the tolerance towards the Pfizer-BioNTech vaccine in allergic patients. To address this issue, we used a questionnaire conducted on-line in a group of medical professionals who were vaccinated with the Pfizer-BioNTech vaccine. A total of 1808 respondents, out of whom 1707 received two doses of the vaccine, returned the questionnaire. Local reactions after injection wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 27 publications
1
45
1
2
Order By: Relevance
“…The basic requirement would be a high level of vaccine coverage, including those over 80 years (at the end of 2018 there were 2.3 million people in Germany ≥85 years of age) [ 26 ]. The data collected in our study with evidence of an extremely low rate of vaccination side effects, as also reported by other studies [ 27 ], especially in those over 80 years of age, may help to motivate the population at large to accept the vaccination, especially the elders of our society.…”
Section: Discussionsupporting
confidence: 85%
“…The basic requirement would be a high level of vaccine coverage, including those over 80 years (at the end of 2018 there were 2.3 million people in Germany ≥85 years of age) [ 26 ]. The data collected in our study with evidence of an extremely low rate of vaccination side effects, as also reported by other studies [ 27 ], especially in those over 80 years of age, may help to motivate the population at large to accept the vaccination, especially the elders of our society.…”
Section: Discussionsupporting
confidence: 85%
“…In a previous report, the COVID-19 vaccination of hospital staff was performed, and the frequency of adverse reactions was examined according to the presence or absence of allergy (11). They found that subjects with a history of allergy had a significantly higher incidence of adverse reactions after vaccination than those without.…”
Section: Discussionmentioning
confidence: 99%
“…According to the currently published literature ( Table 5 ), patients with allergy history apparently had a higher prevalence of local and systemic post-vaccination symptoms compared to subjects with no allergy [ 51 , 54 ]. Specifically, one large study compared the clinical features of patients with allergies receiving the BNT162b2 vaccine with those of subjects from the general population who had no allergy (but could have other comorbidities) and found that allergic subjects had higher rates of local pain (86% vs. 80% in controls), local erythema (17% vs. 11%) and local swelling (19% vs. 13%) throughout the vaccination cycle.…”
Section: Allergic and Mast-cell Disordersmentioning
confidence: 99%
“…Specifically, one large study compared the clinical features of patients with allergies receiving the BNT162b2 vaccine with those of subjects from the general population who had no allergy (but could have other comorbidities) and found that allergic subjects had higher rates of local pain (86% vs. 80% in controls), local erythema (17% vs. 11%) and local swelling (19% vs. 13%) throughout the vaccination cycle. The same study reported higher rates of systemic symptoms such as fatigue (50% vs. 45%) and arthralgia (32% vs. 26%) along with headache (42% vs. 37%), gait disturbances (2% vs. <1%), vomit (3% vs. 1%) and palpitations (7% vs. 4%) in allergic individuals compared to non-allergic individuals after the second dose of the BNT162b2 vaccine [ 54 ]. Another study, showed that patients with autoimmunity or immunodeficiency who also had an allergic background had a higher likelihood of experiencing local and constitutional symptoms with the BNT162b2 vaccine [ 51 ].…”
Section: Allergic and Mast-cell Disordersmentioning
confidence: 99%
See 1 more Smart Citation